The Influence of Organizational Citizenship Behavior and Intrinsic Motivation on Employee Performance at BPJS Employment Surabaya Karimunjawa - Novriza Kurniawan; Dwiarko Nugrohoseno (Jurnal Ilmu Manajemen, 2026)
This study aims to examine and analyze the influence of organizational citizenship behavior and intrinsic motivation on employee performance at BPJS Employment Surabaya Karimunjawa. This study uses a quantitative approach. The population used is all employees of BPJS Employment Surabaya Karimunjawa, and the sample size collected is 31 respondents. The sampling technique used was saturation sampling, meaning that all employees in the population were included as samples. The data in this study were analyzed using SPSS version 25. The results of this study indicate that organizational citizenship behavior does not significantly influence employee performance, while intrinsic motivation significantly influences employee performance.